World Accumulation and Planetary Life, or, Why Capitalism Will Not Survive until the ‘Last Tree is Cut - Moore, Jason W. (UI Scholars Hub, 2019)
How does capitalism work through the web of life? How can we begin to understand capitalism not simply as an economic system of markets and production and a social system of class and culture, but as a way of organising nature? This essay explores a relational, historical, and geographical answer to these questions. Arguing that capitalism is a world-ecology that joins the accumulation of capital, the pursuit of power, and the co-production of webs of life in dialectical unity, Moore offers a way to understand today’s planetary crisis. That crisis marks a turning point not only in the planet’s climate system, but in ways of organization power, production, and reproduction over the past five centuries. Planetary justice in the twenty-first century will need to make sense of catastrophic climate change not just as matter of too many greenhouse gases, but also as a moment of the climate class divide, climate patriarchy, and climate apartheid.